Chemical Studies on the Roots of the Saudi Date Palm Tree — Phoenix Dactylifera L - S. Al-Showiman, Salim; A. Ba Osman, Ahmad (Asian Journal of Chemistry, 2010)
Petroleum ether extracts, ethyl alcohol extracts as well as ashed material of the roots of the date palm tree (Phoenix dactylifera L.) of cultivar Maktomey were analysed by gas-liquid chromatography, 1H/13C NMR spectroscopy and atomic absorption spectrophotometry. They were found to contain fixed oil, sugars and other significant organic and inorganic compounds. Although a very small quantity of fatty acids was extracted out, carbohydrates were found to be present in significant amounts. Mineral contents like Ca, Fe, K, Mg, Na and Zn were determined in the ashed material, with Na in dominant strength in the range of 2194.42 μg/g.